(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2009)
Dielectric relaxation behavior of sodium dodecylsulfate in aqueous solutions of dimethylsulfoxide has been investigated by virtue of dielectric relaxation spectroscopy. It has been shown that in the ternary system SDS–water–DMSO stable micelles are formed at XDMSO=0.2 and CSDS=0.025 M.